Continuous process troubleshooting DCS I/Os : practices - Primedia Workplace Learning ([United States] : PRIMEDIA Workplace Learning)
The Troubleshooting DCS I/Os: Practices training program, or unit, is designed to familiarize trainees with some practical applications of basic procedures for troubleshooting the inputs and outputs of a distributed control system. After completing this program, the trainees should be able to explain how to troubleshoot problems in digital I/O devices that are part of a DCS, analog I/O devices that are part of a DCS, and miscellaneous I/O components of a DCS.
Keywords: Electric controllers -- Maintenance and repair; Electric controllers; Electric motors -- Electronic control